Alterations of gut microbiota in infants with biliary atresia identified by 16S rRNA-sequencing - Fei Liu; Ru Wei; Xiaogang Xu; Menglong Lan; Boyuan Tao; Zijian Liang; Jixiao Zeng (BMC, 2024)
Abstract Background Biliary atresia (BA) is a severe neonatal disease with progressive intra- and extra-hepatic bile ducts inflammation and hepatic fibrosis. Characterization of gut microbiome profiles in infants with biliary atresia can provide valuable information and potential disease biomarkers. Our study aims to explore the relationship between gut microbiota and biliary atresia. Methods 16 S ribosomal RNA (rRNA) gene sequencing was carried out to identify the differences in composition and diversity of gut microbiota between infants with BA and healthy subjects. A total of 31 infants with biliary atresia and 20 healthy subjects were recruited. Results The composition of gut microbiota in BA group was significantly different with the normal control group (P < 0.05) and the abundance ratio of Klebsiella/Bifidobacterium showed great potential for identification of BA (P < 0.01). In addition, the differential bacterial taxa were involved in lipid and vitamins metabolism. Conclusion Our results could provide potential non-invasive biomarker for identification of biliary atresia and contribute to the treatment in terms of ameliorating microbiota dysbiosis.